Autoimmune Thyroid Disease in Rheumatoid Arthritis: A Global Perspective. (18th November 2012) - Cárdenas Roldán, Jorge; Amaya-Amaya, Jenny; Castellanos-de la Hoz, Juan; Giraldo-Villamil, Juliana; Montoya-Ortiz, Gladys; Cruz-Tapias, Paola; Rojas-Villarraga, Adriana; Mantilla, Rubén D.; Anaya, Juan-Manuel
Abstract : Objective . To determine the prevalence and impact of autoimmune thyroid disease (AITD) in patients with rheumatoid arthritis (RA). Methods . Eight-hundred patients were included. The association between AITD and RA was analyzed was analyzed by bivariate and multivariate analysis. In addition, a literature review was done focusing on geographical variations. Results . In our cohort the prevalence of AITD was 9.8% while the presence of antibodies was 37.8% for antithyroperoxidase enzyme (TPOAb) and 20.8% for antithyroglobulin protein (TgAb). The presence of type 2 diabetes, thrombosis, abnormal body mass index, and a high educational level was positively associated with AITD. The literature review disclosed a geographical variation of AITD in RA ranging from 0.5% to 27%. Autoantibody prevalence ranges from 6% to 31% for TgAb, 5% to 37% for TPOAb, and from 11.4% to 32% for the presence of either of the two. Conclusion . AITD is not uncommon in RA and should be systematically assessed since it is a risk factor for developing diabetes and cardiovascular disease. These results may help to further study the common mechanisms of autoimmune diseases, to improve patients' outcome, and to define public health policies. An international consensus to accurately diagnose AITD is warranted.